2001
DOI: 10.1111/j.1654-1103.2001.tb02624.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐annual variation in primary production of a semi‐arid grassland related to previous‐year production

Abstract: Mean annual precipitation accounts for a large proportion of the variation in mean above‐ground net primary production (ANPP) of grasslands worldwide. However, the inter‐annual variation in production in any grassland site is only loosely correlated with precipitation. The longest record of variation in production and precipitation for a site corresponds to a shortgrass steppe in Colorado, USA. A previous study of this record showed that current‐year precipitation accounted for 39% of the inter‐annual variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(41 citation statements)
references
References 20 publications
3
36
0
Order By: Relevance
“…Previous studies in grasslands have reported a correlation between current and previous-year precipitation with ANPP and implied causality (Lauenroth and Sala 1992, Knapp et al 1998, Jobba´gy and Sala 2000, Oesterheld et al 2001. We suggest that this work represents a step forward in our understanding because it experimentally tested the hypothesis of the lags and it proposes a mechanism.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies in grasslands have reported a correlation between current and previous-year precipitation with ANPP and implied causality (Lauenroth and Sala 1992, Knapp et al 1998, Jobba´gy and Sala 2000, Oesterheld et al 2001. We suggest that this work represents a step forward in our understanding because it experimentally tested the hypothesis of the lags and it proposes a mechanism.…”
Section: Discussionmentioning
confidence: 53%
“…If the previous year had conditions conducive to high flowering rates, then many of the individuals who flowered the previous year may not have the resources necessary to flower in the current year regardless of environmental conditions. Evidence for lagged effects of precipitation on ANPP has been found in other systems (Cable 1975; Oesterheld et al. 2001; Wiegand et al.…”
Section: Introductionmentioning
confidence: 58%
“…The previous year’s climate has been shown to play a role in determining ANPP in other systems (Cable 1975; Oesterheld et al. 2001; Wiegand et al.…”
Section: Discussionmentioning
confidence: 99%
“…In semiarid systems, the cover of clonal forage grasses can be highly variable from year to year (Craddock and Forsling 1938, Lauenroth and Sala 1992, Oesterheld et al 2001. Because the importance of growth, survival, and recruitment vary with genet size, the size distribution of the populations may help to inform management strategies.…”
Section: Population Structurementioning
confidence: 99%